2023 11th International IEEE/EMBS Conference on Neural Engineering (NER) 2023
DOI: 10.1109/ner52421.2023.10123743
|View full text |Cite
|
Sign up to set email alerts
|

Networks of Injectable Microdevices Powered and Digitally Linked by Volume Conduction for Neuroprosthetics: a Proof-of-Concept

Abstract: Wireless power transfer (WPT) methods such as inductive coupling and ultrasounds are used as an alternative to electrochemical batteries to energize active implantable medical devices. However, existing WPT methods require the use of bulky components (e.g., coils) that hinder miniaturization. To avoid this, we proposed the use of volume conduction of high frequency (HF) current bursts to power and bidirectionally communicate with threadlike implants that can be used for electrical stimulation and sensing (e.g.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…However, it must be noted that the designed communication protocol allows the control of up to 256 devices per low-level control unit, and the possibility to have several low-level units connected to a high-level controller. In fact, we have in vitro demonstrated that more than 10 floating devices can be wirelessly powered and digitally controlled from the external system [38].…”
Section: Discussionmentioning
confidence: 99%
“…However, it must be noted that the designed communication protocol allows the control of up to 256 devices per low-level control unit, and the possibility to have several low-level units connected to a high-level controller. In fact, we have in vitro demonstrated that more than 10 floating devices can be wirelessly powered and digitally controlled from the external system [38].…”
Section: Discussionmentioning
confidence: 99%